Pendidikan Dan Akhlak Di Era Globalisasi - Ahmad Suradi (At-Ta'lim : Media Informasi Pendidikan Islam, 2014)
Globalization has been started. At all quarters of the world, societies become depend on each other in all aspects, such as culture, economic, and politic. Mainly at cultural aspects, the limit of cultural boundaries have gone. This era is a challange for education world. Therefore, this article focused on how moral values become concernt educational process, because it is one of education goals. To prepare human who hold moral values in the globalization era, exactly the educational institution can not exit alone, even though it still hold the main role. All societies, mainly family, must prepare human source who have moral integrity. In practic, educational institution has double roles, at one side must make society conscious to filter globalization mainstream, and at another side it is that the main task to form studen who have personalization.